2022
DOI: 10.1371/journal.pone.0274579
|View full text |Cite|
|
Sign up to set email alerts
|

Emphasizing speed or accuracy in an eye-tracking version of the Trail-Making-Test: Towards experimental diagnostics for decomposing executive functions

Abstract: The Trail-Making-Test (TMT) is one of the most widely used neuropsychological tests for assessing executive functions, the brain functions underlying cognitively controlled thought and action. Obtaining a number of test scores at once, the TMT allows to characterize an assortment of executive functions efficiently. Critically, however, as most test scores are derived from test completion times, the scores only provide a summary measure of various cognitive control processes. To address this problem, we extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 67 publications
3
22
0
Order By: Relevance
“…However, well-established experimental effects often suffer from a variance restriction between individuals when put into settings investigating individual differences (Hedge et al, 2018 ). To corroborate the correlational analyses, we tested whether the alerting effects were experimentally or individually dominated within the respective experiments and dependent measures following a procedure developed by Recker et al ( 2022 ). That is, we compared the variance in the data explained by the experimental effect with the variance due to individual variability.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, well-established experimental effects often suffer from a variance restriction between individuals when put into settings investigating individual differences (Hedge et al, 2018 ). To corroborate the correlational analyses, we tested whether the alerting effects were experimentally or individually dominated within the respective experiments and dependent measures following a procedure developed by Recker et al ( 2022 ). That is, we compared the variance in the data explained by the experimental effect with the variance due to individual variability.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that alerting effects in the simple choice reaction task (Experiment 2) were dominated by the experimental manipulation, that is the alerting cue condition compared with the no cue condition, whereas alerting effects in the more complex TMT-task (Experiment 1) were dominated by variation between individuals (cf. Recker et al, 2022 ). The experimental dominance in the choice task indicates that participants’ alerting effects were highly similar and stereotypical, which should have cut the available variance between individuals, and in this way reduced any correlation between the alerting effects in the two tasks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations